Investigation of ground and isomeric states of exotic nuclei using advances in multiple-reflection time-of-flight mass spectrometry: Unraveling riddles surrounding the proton-emitting isomer(s) in 94Ag - Kripko-Koncz, Gabriella; Justus Liebig University Giessen (My University, 2025)
The mass of an atomic nucleus, i.e. its nuclear binding energy, reflects its nuclear structure, stability and shape. High-precision mass measurements of exotic nuclei with extreme proton-to-neutron ratios allow to study the evolution of nuclear shell closures, the onsets of deformation, the presence of metastable (isomeric) states, the synthesis of heavy elements in the universe and many more striking phenomena. There exists a particularly striking example of an isomeric state in the vicinity of 100Sn, a spin-trap isomer in 94Ag with spin-parity of (21+), which is known to possess properties that are unique in the entire Chart of Nuclei. This isomer has been reported to have multiple decay channels, such as beta decay, beta-delayed proton emission, direct one-proton (1p) decay and, surprisingly, even direct two-proton (2p) decay, out of which the latter two observations have puzzled the nuclear physics community for the last 20 years. The powerful technique of multiple-reflection time-of-flight mass spectrometry (MR-TOF-MS), which enables to perform accurate mass measurements of nuclei with half-lives down to a millisecond, was used in this work to study different ground and isomeric states in medium-heavy exotic nuclei and, ultimately, to further unravel the riddles surrounding the 1p/2p-decay branches of 94Ag. The data acquisition and analysis developments, implemented in this work, allowed to fully exploit the capabilities of the used MR-TOF-MS setups. These developments include, e.g., the validation and fine-adjustments of a software package, which allows for the simulation of the expected TOF spectra, the completion of systematic studies of the mass uncertainty using broadband mass measurements with relative mass-to-charge windows of more than 10% and the assurance of a quick and reproducible change of the operation mode of an MR-TOF-MS from longer flight times, enabling higher mass resolving powers, to shorter cycle lengths, allowing access to nuclei with small half-lives of a few milliseconds. The MR-TOF-MS of TRIUMF‘s Ion Trap for Atomic and Nuclear Science in Vancouver, Canada was used to measure the mass of neutron-rich indium isotopes across the N=82 shell closure. This includes the first mass measurement of the nuclides 133In ,134In and the first direct mass measurement of the nuclide 132In. Furthermore, the measured indium isotopes possess multiple isomeric states with varying excitation energies and half-lives, many of which were observed in this work including, e.g., the first-time measurement of the excitation energy of the 1/2- isomer in 133In, the significant uncertainty reduction of the excitation energies of two high-lying isomers in 127In and 131In, and the observation of a short-lived isomer in 125In with half-life of only 5 ms. Overall, these measurements highlight the capabilities of the employed mass measurement and data analysis techniques, the latter of which was tailored in this work to accurately treat the specific data sets containing multiple overlapping peaks. The measurement setup of the FRS Ion Catcher at GSI in Darmstadt, Germany was used to perform the first direct mass measurement of 93Pd, the 1p-decay daughter of the (21+) isomer in 94Ag, which resulted in a mass excess value of -59127(35) keV reducing the mass uncertainty by an order of magnitude. As a consequence, a crucial incompatibility in the previously reported decay scheme of the 1p and 2p branches is found: the measurement shows for the first time beyond doubt that the excitation energies of the presumed parent states of the 1p and 2p decay branches in 94Ag disagree, which calls into question the present interpretation of these decay branches. Three scenarios are discussed, which could resolve this apparent contradiction, and elucidated by performing state-of-the-art shell-model and mean-field calculations. The latter calculations confirm that, based on the reported decay information, the 2p emission cannot be fed from the same (21+) isomer as the 1p emission, but indicate that it could originate from a second, structurally different, high-spin state. This would give possible explanations to almost all historical riddles surrounding these exotic decay modes.
Keywords: Mass spectrometry; Exotic nuclei; Isomeric states; Proton emission; ddc:530